2021
DOI: 10.3389/fcell.2021.663037
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Inflammation-Triggered by Periodontal Ligament Stem Cell Pyroptosis Exacerbates Periodontitis

Abstract: Periodontitis is an immune inflammatory disease that leads to progressive destruction of bone and connective tissue, accompanied by the dysfunction and even loss of periodontal ligament stem cells (PDLSCs). Pyroptosis mediated by gasdermin-D (GSDMD) participates in the pathogenesis of inflammatory diseases. However, whether pyroptosis mediates PDLSC loss, and inflammation triggered by pyroptosis is involved in the pathological progression of periodontitis remain unclear. Here, we found that PDLSCs suffered GSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 54 publications
4
80
0
Order By: Relevance
“…Notable differentially upregulated genes with critical roles in the pathogenesis of HIV infection and periodontal disease ( Figure 1 a ) included IDO1 (a marker of immune activation), 24 25 IL21R (proliferation of T, B, and NK cells), 26 CXCL10 (neutrophil migration and periodontal bone loss) 27 , 28 , 29 , MMP12 (gingival extracellular matrix degradation), 30 31 IRF1 & IRF7 (innate and adaptive immune response) 32 , VCAM1 (leukocyte-endothelial adhesion/migration), 33 LYN (inflammatory response to bacterial LPS), 33 TLR2 (immune response to bacterial lipoproteins and lipopeptides), 34 TRIM5 and SAMHD1 (HIV/SIV restriction), ALOX5AP (Leukotriene synthesis), GZMA and GZMH (chronic inflammation and antiviral response), KLK6 (inflammation), CD163 (anti-inflammatory macrophages) and GSDMD (bactericidal activity). 35 36
Figure 1 Long-term low dose THC administration inhibits proinflammatory gene expression in gingiva of chronically SIV-infected RMs. Volcano plot shows the relationship between fold-change (X-axis) and statistical significance (Y-axis) of differentially expressed mRNAs in VEH/SIV ( a ) and THC/SIV ( d ) RMs relative to controls and in VEH/SIV relative to THC/SIV RMs ( g ).
…”
Section: Resultsmentioning
confidence: 99%
“…Notable differentially upregulated genes with critical roles in the pathogenesis of HIV infection and periodontal disease ( Figure 1 a ) included IDO1 (a marker of immune activation), 24 25 IL21R (proliferation of T, B, and NK cells), 26 CXCL10 (neutrophil migration and periodontal bone loss) 27 , 28 , 29 , MMP12 (gingival extracellular matrix degradation), 30 31 IRF1 & IRF7 (innate and adaptive immune response) 32 , VCAM1 (leukocyte-endothelial adhesion/migration), 33 LYN (inflammatory response to bacterial LPS), 33 TLR2 (immune response to bacterial lipoproteins and lipopeptides), 34 TRIM5 and SAMHD1 (HIV/SIV restriction), ALOX5AP (Leukotriene synthesis), GZMA and GZMH (chronic inflammation and antiviral response), KLK6 (inflammation), CD163 (anti-inflammatory macrophages) and GSDMD (bactericidal activity). 35 36
Figure 1 Long-term low dose THC administration inhibits proinflammatory gene expression in gingiva of chronically SIV-infected RMs. Volcano plot shows the relationship between fold-change (X-axis) and statistical significance (Y-axis) of differentially expressed mRNAs in VEH/SIV ( a ) and THC/SIV ( d ) RMs relative to controls and in VEH/SIV relative to THC/SIV RMs ( g ).
…”
Section: Resultsmentioning
confidence: 99%
“…Experiments in a mouse model of experimental periodontitis confirmed that GSDMD deficiency alleviates periodontal inflammation and bone loss ( 13 ). Moreover, CDK9 inhibition decreases necroptosis and reduces inflammatory bone resorption in mice with bacteria-induced periodontitis ( 99 ).…”
Section: Potential Role For Panoptosis During Oral Infectious Diseasesmentioning
confidence: 97%
“…Notably, elevated levels of RIPK1, phosphorylated RIPK3, MLKL, phosphorylated MLKL, and FLIPL are common in gingival epithelia and connective tissues from CP patients, indicating the presence of necroptosis during progression of periodontitis ( 10 ). Importantly, increased expression of IL-1β in gingival crevicular fluid correlates significantly with the severity of periodontitis ( 13 ). Thus, PANoptosis is thought to be one of the pathogenic mechanisms underlying persistent inflammation observed in periodontal disease.…”
Section: Potential Role For Panoptosis During Oral Infectious Diseasesmentioning
confidence: 99%
“…In clinical practice, clinicians frequently face situations where the periodontal or peri-implant tissues overreact to a stimulus promoted by dental materials or even do not respond to therapies, leading to inflammation. In these situations, the claim is that the body is not accepting the treatment, rehabilitation, or therapy [ 1 , 2 , 3 , 4 ]. Indeed, it is very likely that processes are occurring inside the cells to cause such exacerbated inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the mechanisms of pyroptosis involve different major signalling pathways, all activating the downstream of GSDMD. Finally, cytoplasmic molecules, such as interleukins-1β (IL-1β) and -18 (IL-18), are released from the pores formed by GSDMD and trigger a robust inflammatory response ( Figure 1 ) [ 2 , 9 , 10 ]. Thus, the occurrence of pyroptosis can be determined by a combination of markers, including the activation of caspases-1, -4, -5, and -11, the cleavage of GSDMD, and the maturation and release of IL-1β and IL-18 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%